Computing ship strikes and near miss events of fin whales along the main ferry routes in the Pelagos Sanctuary and adjacent west area, in summer. Issue 3 (13th February 2022) - David, Léa; Arcangeli, Antonella; Tepsich, Paola; Di‐Meglio, Nathalie; Roul, Marine; Campana, Ilaria; Gregorietti, Martina; Moulins, Aurélie; Rosso, Massimiliano; Crosti, Roberto
Abstract: The Mediterranean Sea is a high‐density maritime traffic area, particularly in the Pelagos Sanctuary. Ship strikes pose a substantial threat to fin whales ( Balaenoptera physalus ) according to reports from the IUCN, the IWC, the ACCOBAMS and the EU Habitats Directive. Near miss events (NMEs) were collected, as a proxy indicator of ship strikes for fin whales, along the main ferry routes crossing the Pelagos Sanctuary and adjacent western waters during 'summertime' (April to October). The 'Fixed Line Transect Med Network' carries out systematic surveys from ferries and collects data according to the 'linear transect' method. From 2008 to 2019, 13 different ferry routes were surveyed with 238, 499 km monitored. Of the 2, 775 fin whales encountered, 43 individuals were involved in NMEs (1.55% of the sightings). NMEs occur over the great majority of the routes monitored with enough effort and were correlated with the density index of fin whales. High‐risk areas for NMEs were identified in the central and deeper parts of the north‐western Mediterranean Sea and in some sections of the northern Tyrrhenian Sea. Of all NMEs, the majority of whales (63.4%) surfaced in front of the vessel (<50 m), leaving no time for the crew to manoeuvre the vessel. The others were travelling (26.8%) or resting (9.7%) without any noticeable reaction at the vessel. The speed of the ferries seems to play a role in the occurrence of the NME, as this parameter is significantly different (t‐test, P = 0.002) for NMEs compared to all fin whale sightings, whereas month and hour of day were not. Quantifying NMEs based on real‐time observation with observers on board, could be used as a feasible and efficient way to limit collisions, raising awareness by the crew, and testing or evaluating other potential tools that can help mitigate this threat.